La utopía de la identidad nacional en Le dedico mi silencio (2023): música, literatura y el fracaso del mestizaje cultural [Crítica] - Jaramillo Reinoso, Pablo (2026)
This article analyzes how Le dedico mi silencio, by Mario Vargas Llosa problematizes national identity through criollo music and the failure of mestizaje in Peru. Using an interdisciplinary approach, the study examines the role of music as a symbol of an idealized nation, as well as the protagonist’s final silence as a metaphor for national disillusionment. The analysis is based on the theoretical contributions of García Canclini on cultural hybridity, Huyssen on memory, and Sarlo on the construction of national discourses. The findings suggest that Vargas Llosa not only offers a critique of the utopia of Peruvian identity but also reflects on the role of art in shaping collective memory.